If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4 + -1x) = 5 (4 * 6 + -1x * 6) = 5 (24 + -6x) = 5 Solving 24 + -6x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -6x = 5 + -24 Combine like terms: 24 + -24 = 0 0 + -6x = 5 + -24 -6x = 5 + -24 Combine like terms: 5 + -24 = -19 -6x = -19 Divide each side by '-6'. x = 3.166666667 Simplifying x = 3.166666667
| y/6=-29 | | 7x-5x+x-3+4x= | | 10x-10+2=-20 | | X/3-9=8 | | 9z(3m+5r)= | | 23=2y-17 | | X-7+2x=43 | | 174+(84*x)=1350 | | -(z-8)= | | 6.4x-4+x-1.9= | | -16x+5x=4(3x+7) | | 8+4=20 | | 7(x+33)+9=5(x-2)-3x | | 2t^2-2t+6=0 | | 22n-36=0 | | X^2-1.4x+0.49=0.35 | | 2m+13=16 | | 3(x-2)+5(x-2)=15x | | 3(5x+2)=2(3-6) | | m+17=34 | | 10x-10+2=-26 | | 3x+53=6x-35 | | 4/7x=11/x-3 | | m+17=134 | | 5x-48=-x | | -10y-3y-7=-12 | | 43x=8-4y | | 2c+22=7c-10 | | 3(x+4)+8=-10 | | 2(x-5)-4-5x+1=0 | | x=.5(3x-13) | | 2x+y-76=0 |